2010
DOI: 10.1177/0959683610362813
|View full text |Cite
|
Sign up to set email alerts
|

Indian Summer Monsoon variations could have affected the early-Holocene woodland expansion in the Near East

Abstract: Postglacial expansion of deciduous oak woodlands of the Zagros—Anti-Taurus Mountains, a major biome of the Near East, was delayed until the middle Holocene at ~6300 cal. yr BP. The current hypotheses explain this delay as a consequence of a regional aridity during the early Holocene, slow migration rates of forest trees, and/or a long history of land use and agro-pastoralism in this region. In the present paper, support is given to a hypothesis that suggests different precipitation seasonalities during the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 30 publications
8
88
0
Order By: Relevance
“…Conversely, a late reforestation (only after 8 ka) occurred in the drier parts of the Near East, in sites located in southernmost Europe, and in continental zones. This might be explained by a dry early Holocene where moisture levels were below the tolerance threshold for tree growth or a by a change from summer/spring to winter precipitation in sites located in Anti-Taurus-Zagros Mountains (van Zeist and Bottema, 1991;Stevens et al, 2001;Bottema and Sarpaki, 2003;Wick et al, 2003;Wright et al, 2003;Tzedakis, 2007;Djamali et al, 2010). We can conclude that the northern borderland of Southern Europe can be considered a transitional zone where the moisture level determined an earlier (ca.…”
Section: Valsecchi Et Al: Vegetation Dynamics In the Northeasternmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a late reforestation (only after 8 ka) occurred in the drier parts of the Near East, in sites located in southernmost Europe, and in continental zones. This might be explained by a dry early Holocene where moisture levels were below the tolerance threshold for tree growth or a by a change from summer/spring to winter precipitation in sites located in Anti-Taurus-Zagros Mountains (van Zeist and Bottema, 1991;Stevens et al, 2001;Bottema and Sarpaki, 2003;Wick et al, 2003;Wright et al, 2003;Tzedakis, 2007;Djamali et al, 2010). We can conclude that the northern borderland of Southern Europe can be considered a transitional zone where the moisture level determined an earlier (ca.…”
Section: Valsecchi Et Al: Vegetation Dynamics In the Northeasternmentioning
confidence: 99%
“…Recently, climate simulations have shown that across the early Holocene stronger winter precipitation occurred over the Northeastern Mediterranean (near Turkey), while there is little evidence for summer precipitation in the Eastern Mediterranean (Brayshaw et al, 2011). The mechanism associated with winter precipitation in Eastern Mediterranean is not yet fully understood (Giorgi and Lionello, 2008), while it has been shown that strengthening/weakening of the Indian Monsoon is related with increase/decrease in spring precipitation in AntiTaurus-Zagros region (Djamali et al, 2010). Evidence from palaeo-data suggests that negative rainfall anomalies in the Black Sea region occurred during phases of high North Atlantic Oscillations (NAO) causing intervals of lower claylayer frequencies (Lamy et al, 2006).…”
Section: Valsecchi Et Al: Vegetation Dynamics In the Northeasternmentioning
confidence: 99%
“…During interglacial peaks, maximum tree pollen percentages reflect warm conditions and higher precipitation from the mid-latitude westerly system. Changes in seasonality were proposed by several authors to explain Holocene climate in the region (Stevens et al, 2001(Stevens et al, , 2006Magny, 2007;Tzedakis, 2007;Peyron et al, 2010;Djamali et al, 2010). At Yammoûneh, sharp δ c increases in phase with arboreal pollen peaks, attributed to enhanced seasonal thermal and hydrological contrasts, suggest that the hypothesis of seasonal changes is valid for older interglacial stages (e.g., MIS 5.5 and MIS 5.1).…”
Section: Comparison With Other Ems Recordsmentioning
confidence: 99%
“…Quercus brantii (Lindl.) is the most abundant deciduous species through Zagros-Anti-Taurus Mountains in west of the Iranian plateau and its survival is considered to be strongly dependent on early spring precipitation, and is sensitive to long drought periods (Djamali et al, 2010). Despite its wide range of distribution, no dendrochronological evidence of this species is available.…”
Section: Introductionmentioning
confidence: 99%